Involvement of Dendritic Cells and Th17 Cells in Induced Tertiary Lymphoid Structures in a Chronic Beryllium Disease Mouse Model - Alex KleinJan; Menno van Nimwegen; Karolina Leman; Ke-xin Wen; Louis Boon; Rudi W. Hendriks (Hindawi Limited, 2021)
Rationale. Sarcoidosis is a systemic inflammatory disorder characterized by the presence of granulomas in various organs, most commonly in the lungs. Although the ethology is unknown, sarcoidosis is thought to be mediated by T helper (Th)1 and Th17 lymphocytes. Chronic airway exposure to beryllium metal leads to chronic beryllium disease (CBD), which shares similarities with pulmonary sarcoidosis. Objective. To study airway pathophysiology and the role of dendritic cells (DCs) and IL-17 receptor (IL-17R) signals in a mouse model for CBD. Methods. Here, we present a CBD mouse model in which mice were exposed to beryllium during three weeks. We also exposed IL-17R-deficient mice and mice in which DCs were depleted. Results. Eight weeks after the initial beryllium exposure, an inflammatory response was detected in the lungs. Mice displayed inflammation of the lower airways that included focal dense infiltrates, granuloma-like foci, and tertiary lymphoid structure (TLS) containing T cells, B cells, and germinal centers. Alveolar cell analysis showed significantly increased numbers of CD4+ T cells expressing IFNγ, IL-17, or both cytokines. The pathogenic role of IL-17R signals was demonstrated in IL-17R-deficient mice, which had strongly reduced lung inflammation and TLS development following beryllium exposure. In CBD mice, pulmonary DC subsets including CD103+ conventional DCs (cDCs), CD11b+ cDCs, and monocyte-derived DCs (moDCs) were also prominently increased. We used diphtheria toxin receptor-mediated targeted cell ablation to conditionally deplete DCs and found that DCs are essential for the maintenance of TLS in CBD. Furthermore, the presence of antinuclear autoantibodies in the serum of CBD mice showed that CBD had characteristics of autoimmune disease. Conclusions. We generated a translational model of sarcoidosis driven by beryllium and show that DCs and IL-17R signals play a pathophysiological role in CBD development as well as in established CBD in vivo.